THE INTERACTION OF ACTIVITY TRAVEL PATTERN, BUILT ENVIRONMENT AND AFFECTIVE EXPERIENCED ON SOCIAL HEALTH - AHMAD, SYAHMI (Universiti Teknologi PETRONAS, 2020)

(untitled)
According to Hagerstrand (1970), travel is a fixed constraint for peoples to fulfil their need, wants and desires. Individual’s activity-travel pattern can be found in relation with subjective well-being or in this case social health. Activity travel pattern of individual in a built environment can affect the social health whether in good or bad ways possibly. On this project, we study and analyse the activity travel pattern in built environment and how it affect the social health. Furthermore, this paper will explore more about the relationship between activity travel pattern and built environment and how they affect the social health through the intermediate variable of affective experienced which defined as a state of emotions, feelings and moods. By using the 2013 Bandung Metropolitan Area (BMA) dataset. Then the result using the BMA will be analyse using SPSS software that can analyse all multiple variable and quantities at the same time or simultaneously. With that findings, a suggestion on the behaviour and way people develop their activity travel pattern in any form of built environment in order to produce a better and positive affective experienced (emotions, feelings and moods) as driver to a better social health environment resulted.